Eksistensi Ruh Perspektif Syekh Nawawi Al Bantani (Analisis Penafsiran Syekh Nawawi Al Bantani Dalam Tafsir Marah Labid Likasyfi Ma’na Al-Qur’an Al Majid) (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
Mining knowledge from Sheikh Nawawi Al Bantani's monumental work in the interpretation of Marah Labid will never cease, including the theme of the soul as discussed in this article. This writing aims to present Sheikh Nawawi's perspective on the meaning of the soul in his interpretative work, which is characterized by mystical elements with a distinctive Nusantara flavor. The approach taken involves analytical descriptions of the meaning of the soul, followed by a critical analysis and comparison with other interpreters. From Sheikh Nawawi Al Bantani's interpretation of the eloquence of the meaning of the